Pengaruh Kredibilitas Brand Ambassador terhadap Minat Beli Cessa Natural Essential Oil Roll On - Rd. Funny Mustikasari Elita; Ira Mirawati; Muhammad Fauzan Chaidir (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
This research aims to determine whether there is an influence of Expertise, Trustworthiness, and Attractiveness (credibility) of Nagita Slavina and Rayyanza, both simultaneously and partially, as brand ambassadors on the purchase intention of followers of the Instagram account @cessa.official. The research utilizes the Source Credibility Theory proposed by Carl Hovland, Janis, and Kelly in 1953. A quantitative method was employed by distributing a questionnaire via Google Forms to 68 research samples online. The results of this study show that the credibility of Nagita Slavina and Rayyanza as brand ambassadors, which includes Expertise, Trustworthiness, and Attractiveness, has a significant influence, both simultaneously and partially, on the purchase intention of Cessa Essential Oil Roll On among the followers of @cessa.official.